An investigation into the overwintering capability of Istocheta aldrichi (Mesnil) (Diptera: Tachinidae) a parasitoid of Popillia japonica Newman (Coleoptera: Scarabaeidae) on Terceira Island, Azores. - Simões, Ana M. (1999)
A study of diapause in the parasitic fly Istocheta aldrichi (Diptera: Tachinidae) was undertaken to help investigate the possibility of its establishment in Terceira as a biological control agent of the Japanese beetle, Popillia japonica (Coleoptera: Scarabaeidae). It was concluded that pupae should be imported from the USA only when they are almost ready to emerge, and to optimise rearing conditions there to increase emergence percentages. Conditions are not ideal for its development in Terceira, as this univoltine parasitoid has a high pupal mortality both in laboratory cultures and outdoors during the overwintering period. These studies should continue until I. aldrichi has become established in the Azores.